ARTIFICIAL INTELLIGENCE TECHNOLOGIES IN RESEARCH ACTIVITIES: OVERVIEW AND APPLICATION - Oksana Buinytska; Valeriia Smirnova (Неперервна професійна освіта: теорія та практика)
The rapid development of artificial intelligence (AI) technologies is significantly changing approaches to research in the modern educational environment. Thanks to the capabilities of modern technologies, researchers have access to tools that help automate routine processes, facilitate data analysis and interpretation, and increase the accuracy of complex tasks. The study identifies key areas of application of AI tools in research, including search and selection of literature on the research topic, organisation of scientific publications, work with research results, increasing the visibility and dissemination of research results, analysis of the research network and research impact, visualisation of research results, creation of presentations, translation of texts and grammar checking, conversion of audio and video to text. In these areas, the researchers analysed and selected AI-based tools that support the research process. A study of the functionality of common AI tools and ways to use them in research activities was carried out. The positive impact of using AI tools in the preparation of research results is confirmed by the results of a survey of young researchers, in particular, AI tools simplify the process of working with scientific sources, interpreting and analysing data, facilitate the creation of visualisations, graphs, charts, and help increase the visibility, dissemination and impact of research results. However, the use of artificial intelligence technologies poses a number of challenges and risks, including the risk of violating the principles of academic integrity and ethics, so it is important to comply with the principles of ethical and responsible use of AI technologies in research.